The Effects of Lyophilization on the Physico-Chemical Stability of Sirolimus Liposomes - Ghanbarzadeh, Saeed (Tabriz University of Medical Sciences, 2013)
Purpose: The major limitation in the widespread use of liposome drug delivery system is its instability. Lyophilization is a promising approach to ensure the long-term stability of liposomes. The aim of this study was to prepare sirolimus-loaded liposomes, study their stability and investigate the effect of lyophilization either in the presence or in the absence of lyoprotectant on liposome properties. Methods: Two types of multi-lamellar liposomes, conventional and fusogenic, containing sirolimus were prepared by modified thin film hydration method with different ratio of dipalmitoylphosphatidylcholine (DPPC), cholesterol and dioleoylphosphoethanolamine (DOPE), and were lyophilized with or without dextrose as lyoprotectant. Chemical stability investigation was performed at 4°C and 25°C until 6 months using a validated HPLC method. Physical stability was studied with determination of particle size (PS) and encapsulation efficiency (EE %) of formulations through 6 months. Results: Chemical stability test at 4°C and 25°C until 6 months showed that drug content of liposomes decreased 8.4% and 20.2% respectively. Initial mean EE % and PS were 72.8 % and 582 nm respectively. After 6 months mean EE % for suspended form, lyophilized without lyoprotectant and lyophilized with lyoprotectant were 54.8 %, 62.3% and 67.1 % at 4°C and 48.2%, 60.4 % and 66.8 % at 25°C respectively. Corresponding data for mean PS were 8229 nm, 2397 nm and 688nm at 4°C and 9362 nm, 1944 nm and 737 nm at 25°C respectively. Conclusion: It is concluded that lyophilization with and without dextrose could increase shelf life of liposome and dextrose has lyoprotectant effect that stabilized liposomes in the lyophilization process.